PEMBELAJARAN BERBASIS KOMUNITAS DAN PEMBERDAYAAN PEREMPUAN DESA: ANALISIS TREN, TEMA, DAN ARAH PENELITIAN MELALUI PENDEKATAN BIBLIOMETRIK - Afina Rahma Hadiyati; Agus Afandi (LPPM Universitas Negeri Surabaya, 2025)
This study analyzes the publication patterns, knowledge structure, and research directions on community-based learning and rural women’s empowerment through a bibliometric approach. The research uses the Scopus database and applies a Boolean query combining community-based learning, women empowerment, rural area, and participatory approach. The analysis reveals three major findings: the researcher collaboration map, the conceptual constellation of keywords, and the distribution of publication sources. The collaboration map shows a transnational yet limited research network with interdisciplinary characteristics. The conceptual map indicates strong connections among empowerment, participation, community, and rural women, reflecting the role of community spaces in knowledge production and social transformation for women. The distribution of publications across nine journals demonstrates that the topic has not yet formed a consolidated academic domain. The findings highlight the need for theoretical and methodological consolidation to advance critical education, rural feminist studies, and participatory research within sustainable development discourse. This study contributes as an initial scientific mapping to strengthen future research agendas and identify knowledge gaps in community-based women’s empowerment studies. Keywords: community-based learning; rural women’s empowerment; bibliometric analysis; research collaboration; rural community studies